The causes of real exchange rate movements - Beate Reszat (Intereconomics, 1985)
Increasing exchange rate fluctuations, such as those that have occurred in the US dollar, have recently revived the discussion about the causes of such movements and the criteria for calculating the long-term over- or undervaluation of a currency. This article stresses some aspects that have attracted little attention hitherto.
Keywords: 330